Penerapan Senam Hamil dalam Penguatan Edukasi Kesehatan bagi Ibu Hamil - Yizri Novfrida; Rangga Pusmaika; Eva Fitriana br. Sirait; Hesti Istyorini (LPPM Akbid Harapan Ibu Pekalongan, 2025)
WHO recommends that pregnant women engage in moderate intensity physical activity for at least 150 minutes per week during pregnancy and during postpartum. One form of physical activity during pregnancy can be done through pregnancy exercises. The aim of this community service activity is to improve the quality of antenatal care which is carried out by providing information and teaching pregnancy exercises to third trimester pregnant women who take part in the pregnancy class at the Az-Zahra Clinic, Tangerang City. This community service activity was carried out twice on Saturday, July 6 2024 and Saturday, July 13 2024 at the Az-Zahra Clinic, Tangerang City. The method used is counseling regarding the importance of implementing pregnancy exercises during pregnancy using power point media and implementing pregnancy exercise exercises accompanied by midwives and midwifery students who have received previous pregnancy exercise training. The participants were 12 pregnant women in the second and third trimesters. Community service activities are divided into preparation stages, activity implementation, and activity evaluation. It is hoped that this activity of implementing pregnancy exercise will continue to be sustainable, and can be carried out independently by every pregnant woman at home with the assistance of a midwife. So, through the implementation of pregnancy exercises you can optimize the health of the mother and fetus, and prepare for a safe, normal delivery.